Digital Apostleship: Evangelization in the New Agora - Galang, Justine Renus F. (Religions, 2021)
The digital space is understood not as a parallel and antithetical component of one’s lived existentiality but a significant and substantial component of human existence that if ethically considered can be a platform for realizing religious identity, mission, and vocation. In this paper, social media platforms are argued as the new digital agoras that reflect the dynamics of the ancient Greek agoras. The nexus of interaction between the social media as the new agora and the Christian vocation and mission of evangelization and apostleship is the point of realized commitment among Christians to take part in the formation of a culture of synodality through an empowered and engaged presence in social media. Divided into two parts, the paper tackles social media platforms as the new agoras of the contemporary world and delves into a theological exploration of the digital apostleship in the new agoras with particular stress on the universality of the vocation and its potential contribution toward realizing the vision of a synodal Church.